Plastics in engineering, - Delmonte, John (Machine design series, 1940)
Introduction to organic plastics - Nomenclature, types and chemistry of organic plastics - Characteristics and preparation of molding compositions - Effects of fillers on properties of molded plastics - Laminated plastics and their manufacture - Cast phenolics and extruded plastic materials - Physical, thermal, electrical and chemical properties of plastics - Design and specification of plastics for production - Design principles for molded plastic parts - Factors affecting the hot molding of plastics - Hot molding of plastics, methods and procedure - Cold molding of plastics, materials and operations - Molds for plastics, their construction and design - Nonmetallic gears and pinions - Nonmetallic cams, couplings and clutches - Engineering applications of plastics - Engineering applications of transparent plastics - Styling the machine with plastics - Fabrication and finishing plastic materials - Organic plastics in surface coatings - Synthetic rubbers and rubber-like resins - Common failures and defects in plastic materials - Test methods applicable to plastics - Comparative costs of plastics and molds - Trends in plastics.